Practical Model of Organizational Personnel Competence Initiation Via Competency Based Interview - Djamil Hasim (Program Pascasarjana Universitas Negeri Makassar, 2019)
The phenomenon of the quality of human resources in organizations, commonly discussed in a broad general framework. Even the arguments presented in the general context even tend to lose practical focus, including when examining the competence of organizational personnel. In this study, experimentation is carried out by placing competencies as initial access to the quality of organizational personnel resources, then the focus is directed at the recruitment program. This study considers that the recruitment program is the first opportunity for the organization to pay attention to the ability (quality of HR) of prospective personnel who will work later. This perspective brings us to the importance of professional recruitment filtration design and integrity in its implementation. The two aspects support one another, including in; (1) The recruitment filtration process that applies the interview mechanism requires the design of competency-based interviews whose details are examined; (2) Competency-based interview design is implemented with blind professional integrity. For this reason, this study presents a practical model of competency-based interview design that is ready to be implemented with a single condition, blind professional integrity.